Multidimensional time-resolved spectroscopy of vibrational coherence in biopolyenes - Buckup, Tiago; Motzkus, Marcus (Annual review of physical chemistry, 2014)
Multidimensional femtosecond time-resolved vibrational coherence spectroscopy allows one to investigate the evolution of vibrational coherence in electronic excited states. Methods such as pump-degenerate four-wave mixing and pump-impulsive vibrational spectroscopy combine an initial ultrashort laser pulse with a nonlinear probing sequence to reinduce vibrational coherence exclusively in the excited states. By carefully exploiting specific electronic resonances, one can detect vibrational coherence from 0 cm−1 to over 2,000 cm−1 and map its evolution. This review focuses on the observation and mapping of high-frequency vibrational coherence for all-trans biological polyenes such as β-carotene, lycopene, retinal, and retinal Schiff base. We discuss the role of molecular symmetry in vibrational coherence activity in the S1 electronic state and the interplay of coupling between electronic states and vibrational coherence.
First published online as a Review in Advance on November 18, 2013
Gesehen am 28.09.2020